8. KEKERASAN DALAM SENGKETA PERTANAHAN DI INDONESIA - Astuti, Puji (Faculty of Social and Political Sciences Diponegoro University, 2008)
Violence could be define as using power, force and pressure which is act by people to the other. Collective violence connecting with agrarian conflict in Indonesia was be trusted as the result of expropriation of land from the peasant. Violence fundamentally not being rational method, and then became rational method for the peasant because legal method failed to met their need about justice. Along Suharto’s Regime, almost peasant in all around Indonesia have been the victim of land claiming. For this reason, nowdays peasant in almost of region in Indonesia have to start again taking by force their land.